Computed Tomography Derived Coronary Triangulated Orifice Area—Deduction of a New Parameter for Follow-up After Surgical Correction of Anomalous Aortic Origin of Coronary Arteries and Call for Validation - Meijer, Fleur M. M.; Kiès, Philippine; Verheijen, Diederick B. H.; Vliegen, Hubert W.; Jongbloed, Monique R. M.; Hazekamp, Mark G.; Lamb, Hildo J.; Egorova, Anastasia D. (Frontiers in Cardiovascular Medicine, 2021)
Introduction Anomalous aortic origin of a coronary artery (AAOCA) from the opposite sinus of Valsalva is a rare congenital abnormality. Computed tomography angiography (CTA) is primarily used as a diagnostic tool to evaluate the anatomy and identify potentially malignant AAOCA variants. Limited data is available on the role of CTA during post-operative follow-up. We aimed to develop an objective CTA derived parameter for diagnostic evaluation and follow-up after surgical correction of AAOCA and correlate the anatomical features to the postoperative outcome. Methods All consecutive patients who underwent surgical repair of AAOCA from 2001 to 2018 and had pre and post-operative CTA imaging available were included. A retrospective analysis of the pre- and postoperative CTA and the outcomes was performed. The origin and course of the anomalous coronary artery and the ostial dimensions were evaluated and correlated with restenosis of operated coronary artery. To allow an accurate evaluation of the effective orifice area at diagnosis and after surgical repair we deduce and propose a new parameter - the coronary triangulated orifice area (CTOA). Results Out of the 54 patients who underwent surgical treatment for AAOCA, 11 fulfilled the inclusion criteria. The median follow-up was 19 months [IQR 3;42]. The mean age at surgery was 41 ± 16 years, with 6 patients (55%) being male. Postoperatively, the angle between the proximal coronary artery and the aortic wall increased from 20 ± 5° to 28 ± 9° (p<0.01) and ostial diameter in the transversal plane increased from 4.1 ± 2.5mm to 6.2 ± 2.7mm (p<0.01). The median CTOA increased significantly from 1.6 mm² [IQR 0.9;4.9] to 5.5 mm² [IQR 3;11.8] (p<0.005). During follow-up, in 3 patients a restenosis of the operated coronary artery was suspected. In these patients, the CTOA only showed a limited postoperative increase of ≤ 1.4 mm². Conclusions CTA can play an important role in the evaluation of the pre- and postoperative anatomy in AAOCA patients. CTOA may be of use in conjunction with the acute angle take-off and ostial diameter order to comprehensively evaluate the operated ostium after unroofing or patch angioplasty. This requires further technical and clinical evaluation.